KEWENANGAN PENGADILAN PAJAK DALAM MEMUTUS SENGKETA GUGATAN DI BIDANG KEPABEANAN - Romadhani Setio Prabowo; Hedwig Adianto Mau; Rotua Valentina Sagala (Bajang Institute, 2025)
The Tax Court, established under Law Number 14 of 2002 concerning the Tax Court, is a specialized judicial body under the jurisdiction of the Supreme Court. This court is authorized to resolve disputes in the field of taxation, including customs matters. The Tax Court has the authority to adjudicate disputes based on Article 31(1) of Law Number 14 of 2002 concerning the Tax Court.This study falls within the category of normative juridical research. The author employs three approaches: the statute approach, the case approach, and the conceptual approach. Data were obtained from secondary data collected through library research or documentary study in the form of primary legal materials and secondary legal materials, analyzed qualitatively.The research findings indicate that the authority of the Tax Court in resolving customs disputes is regulated under Article 31 of Law Number 14 of 2002 on the Tax Court, which includes both appeals and lawsuits. However, Article 95 of Law Number 17 of 2006 on Customs limits legal remedies against the Reassessment of Tariff and/or Customs Value (SPKTNP) to the appeal mechanism only, without mentioning lawsuits as a legal option. This inconsistency creates legal uncertainty, as the Tax Court has the authority to examine lawsuits, while Law Number 17 of 2006 on Customs, as a lex specialis, only regulates appeals. Although the Tax Court has the authority to handle both appeals and lawsuits, Article 95 of Law Number 17 of 2006 on Customs, as a lex specialis, restricts legal remedies to appeals only. Therefore, the ideal concept in its application is to affirm the principle of lex specialis derogat legi generali, meaning that lawsuits against decisions of the Directorate General of Customs and Excise (DJBC) should be deemed inadmissible, and appeals should be the sole legitimate legal recourse.